Evaluation of neutron radiation damage in zircaloy fuel clad of nuclear power plants: a study based on PKA and dpa calculations. (January 2020) - Noori-kalkhoran, Omid; Gei, Massimiliano
Abstract: During the lifetime of nuclear power plants, irradiation and mechanical interactions can cause permanent damage to their structural materials. In nuclear reactors, one of the most important of these materials is fuel clad that, in addition to its main role in transferring heat from fuel to coolant, restrains most of the radioactive fission products within its volume. In this article, neutron-induced radiation damage based on Primary Knock-on Atom (PKA) and displacement per atom (dpa) calculations are evaluated on fuel clad in Hot Fuel Assembly (HFA) in a WWER-1000 reactor core as a case study. New couplings of existing nuclear and radiation damage codes and methods are developed for dpa calculations and results are compared together and against experimental results. In the first step, the full reactor core is simulated with MCNPX code (v2.7) to determine the HFA and its relevant neutron-energy spectrum. SPECTER, SPECTRA-PKA and PTRAC card of MCNPX are then employed to evaluate the PKA spectrum under neutron bombardment. Finally, dpa calculated with the Binary Collision Approximation approach is achieved through the use of SRIM-2013 code. A MATLAB interchange program is developed to prepare and transfer the data between the mentioned codes and SRIM. Comprehensive comparisons are performed between results in terms of dpa obtained by (i) NRT calculation (NRT-dpa) (SPECTER and SPECTRA-PKA results), (ii) arc-dpa calculation (MCNPX+arc-dpa), (iii) BCA calculation (PTRAC+SRIM) and (iv) coupled calculation (SPECTRA-PKA+SRIM) (all generations of knock-on atoms and clusters are tracked in the last two methods). These comparisons reveal the portions of damage in Zircaloy due to PKAs, secondary knock-on atoms and cascade atoms, the effect of position-depended PKA and the fraction of displaced atoms that come back to their lattice positions as a result of thermal effects and annealing. Effects of elemental PKA are obtained by means of SPECTRA-PKA code and a visualization map of radiation damage in the clad is presented as an outcome of the SRIM code simulation. Results confirm that value of dpa calculated by MCNPX+arc-dpa is closer to experimental ones as the recombination effect in radiation damage is considered in this method.